Managing Severe Dysgeusia and Dysosmia in Lung Cancer Patients: A Systematic Scoping Review - Spencer, Ana Sofia; da Silva Dias, David; Capelas, Manuel Luís; Pimentel, Francisco; Santos, Teresa; Neves, Pedro Miguel; Mäkitie, Antti; Ravasco, Paula (Frontiers in Oncology, 2021)
Introduction: Lung cancer (LC) is highly prevalent worldwide, with elevated mortality. In this population, taste and smell alterations (TSAs) are frequent but overlooked symptoms. The absence of effective therapeutic strategies and evidence-based guidelines constrain TSAs’ early recognition, prevention and treatment (Tx), promoting cancer-related malnutrition and jeopardizing survival outcomes and quality of life. Objectives: To systematically review the literature on TSAs in LC patients, understand the physiopathology, identify potential preventive and Tx strategies and to further encourage research in this area. Methods: Literature search on English language articles indexed to PubMed, CINALH, SCOPUS and Web of Science using MeSH terms “Lung neoplasms”,“Dysgeusia”, “Olfaction Disorders”, “Carcinoma, Small Cell”,“Carcinoma, Non- Small-Cell Lung “Adenocarcinoma of Lung”,“Carcinoma, Large Cell”, and non-MeSH terms “Parageusia”, “Altered Taste”, “Smell Disorder”, “Paraosmia”, “Dysosmia”,“Lung Cancer” and “Oat Cell Carcinoma”. Results: Thirty-four articles were reviewed. TSAs may follow the diagnosis of LC or develop during cancer Tx. The estimated prevalence of self-reported dysgeusia is 35-38% in treatment-naive LC patients, and 35-69% in those undergoing Tx, based on studies involving LC patients only. One prospective pilot trial and 1 RCT demonstrated a clinically significant benefit in combining flavor enhancement, smell and taste training and individualized nutritional counselling; a systematic review, 1 RCT and 1 retrospective study favored using intravenous or oral zinc-based solutions (150mg 2-3 times a day) for the prevention and Tx of chemotherapy (CT) and radiotherapy (RT) -induced mucositis and subsequent dysgeusia. Conclusions: This is the first review on dysgeusia and dysosmia in LC patients to our knowledge. We propose combining taste and smell training, personalized dietary counselling and flavor enhancement with oral zinc-based solutions (150mg, 2-3 times a day) during CT and/or RT in this population, in order to prevent and help ameliorate Tx-induced dysgeusia and mucositis. However due to study heterogeneity, the results should be interpreted with caution. Developing standardized TSA measurement tools and performing prospective randomized controlled trials to evaluate their effect are warranted.